2000
DOI: 10.12693/aphyspola.97.59
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Stability in Kondo Insulators

Abstract: We report on magnetic measurements and electronic structure investigations of CeNiSn and CeRhSb. Both belong to the group of Kondo insulators. The magnetic susceptibility shows the nonmagnetic ground state for these compounds and their alloys. The 3d X-ray photoemission spectroscopy spectra show evidence for the mixed valence state of Ce in CeRhSb alloys, as also seen for CeNiSn, whereas the spectra for the La substituted (Ce,La)NiSn compounds show only evidence for a pure Ce 3+ ground state. We suggest the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Note that CeRhX spectra have weak 4f 0 final-state peak, such as that seen in CePtSn at 2 eV, indicating much higher T K . [7,8] This result suggests the presence of strong valence fluctuations in these compounds, in agreement with transport and magnetic measurements [1,4]. Due to the spin-orbit interaction, the 4f 1 final-state peak in CePtSn is split into the 4f 1 7/2 peak at 220 meV and the 4f 1 5/2 peak (or a tail of the Kondo resonance) at E F .…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Note that CeRhX spectra have weak 4f 0 final-state peak, such as that seen in CePtSn at 2 eV, indicating much higher T K . [7,8] This result suggests the presence of strong valence fluctuations in these compounds, in agreement with transport and magnetic measurements [1,4]. Due to the spin-orbit interaction, the 4f 1 final-state peak in CePtSn is split into the 4f 1 7/2 peak at 220 meV and the 4f 1 5/2 peak (or a tail of the Kondo resonance) at E F .…”
supporting
confidence: 83%
“…Hexagonal (ZrNiAl-type) CeRhSn has attracted much interest because of its non-Fermi liquid (NFL) behavior at low temperatures. [1] The NFL behavior has been discussed from the viewpoint of the proximity to the quantum critical point (QCP), or the existence of the Griffith phase where the intersite Kondo effect and the Ruderman-Kittel-Kasuya-Yoshida (RKKY) interaction are competing due to lattice disorder. [1][2][3] Recently Kim et al synthesized a CeRhSn single crystal, and revealed strong anisotropy in the resistivity (ρ) and magnetic susceptibility (χ).…”
mentioning
confidence: 99%
“…Strong valence fluctuations have been found in all synthesized representatives of CeRhSb 1−x Sn x system [12]. Such instabilities of Ce valency are believed to play an important role in the pseudogap formation for x < x c [15].…”
Section: Introductionmentioning
confidence: 93%
“…We have recently shown [7,8] that CeRhSn exhibits NFL temperature dependencies in its low-temperature physical properties. However, magnetization M and specific heat C, reveal the presence of a very weak magnetic phase transition at 6.2 K. This phase transition observed in the C(T ) data is strongly dependent on the annealing of the polycrystalline sample, while magnetic susceptibility data collected in low magnetic fields reveal spin-glass behaviour.…”
Section: Introductionmentioning
confidence: 99%